Case report and literature review: Malignant adenomyoepithelioma after breast augmentation - Hu, Longqing; Qian, Bei; Yan, Zhecheng; Bing, Kaijian; Mei, Li; Qu, Xincai (Frontiers in Surgery, 2022)
Background: The breast malignant adenomyoepithelioma (MAME) after breast augmentation has never been reported. Case summary: We reported a case of 55-year-old woman who was diagnosed with breast MAME 16 years after breast augmentation. The patient performed the breast augmentation with two 200ml round textured prostheses in the subpectoral plane through axillary incisions in 2004. However, breast ultrasound in 2020 revealed a suspicious malignant lump in the right breast, which was finally confirmed as MAME by pathology. The skin-sparing radical mastectomy and immediate breast reconstruction with expander implantation was performed. Subsequently, the patient was received three cycles of chemotherapy with the regimen of anthracycline and cyclophosphamide. In the following nearly two years of follow-up, no tumor recurrence and metastasis were found, and the overall treatment was satisfied by the patient. Conclusion: Here, we present a unique case in which a patient was diagnosed with breast MAME after breast augmentation. The skin-sparing radical mastectomy and immediate breast reconstruction with expander implantation is a feasible approach that yields at least short-term oncological safety and acceptable aesthetic results. However, whether there is a potential relationship between MAME and breast implants remain to be further explored. Meanwhile, due to the rarity of breast MAME, more authoritative strategy considering both oncological safety and aesthetics to seek better long-term therapeutic effects are need.